Past, Present, and Future Atmospheric Nitrogen Deposition - Kanakidou, M.; Myriokefalitakis, S.; Daskalakis, N.; Fanourgakis, G.; Nenes, A.; Baker, A. R.; Tsigaridis, K.; Mihalopoulos, N. (Journal of the atmospheric sciences, 2016)
Reactive nitrogen emissions into the atmosphere are increasing as a result of human activities, affecting nitrogen deposition to the surface and impacting the productivity of terrestrial and marine ecosystems. An atmospheric chemistry–transport model [Tracer Model 4 of the Environmental Chemical Processes Laboratory (TM4-ECPL)] is here used to calculate the global distribution of total nitrogen deposition, accounting for the first time for both its inorganic and organic fractions in gaseous and particulate phases and past and projected changes due to anthropogenic activities. The anthropogenic and biomass-burning Atmospheric Chemistry and Climate Model Intercomparison Project (ACCMIP) historical and RCP6.0 and RCP8.5 emissions scenarios are used. Accounting for organic nitrogen (ON) primary emissions, the present-day global nitrogen atmospheric source is about 60% anthropogenic, while total N deposition increases by about 20% relative to simulations without ON primary emissions. About 20%–25% of total deposited N is ON. About 10% of the emitted nitrogen oxides are deposited as ON instead of inorganic nitrogen (IN), as is considered in most global models. Almost a threefold increase over land (twofold over the ocean) has been calculated for soluble N deposition due to human activities from 1850 to present. The investigated projections indicate significant changes in the regional distribution of N deposition and chemical composition, with reduced compounds gaining importance relative to oxidized ones, but very small changes in the global total flux. Sensitivity simulations quantify uncertainties due to the investigated model parameterizations of IN partitioning onto aerosols and of N chemically fixed on organics to be within 10% for the total soluble N deposition and between 25% and 35% for the dissolved ON deposition. Larger uncertainties are associated with N emissions.